Simultaneous extraction, separation and purification of microbial genomic DNA and total RNA from acidic habitat samples. Issue 3 (10th December 2014) - Xie, Jianping; Yun, Hui; Dong, Haigang; Zhao, Wenya; Wang, Guohua; Qiu, Guanzhou; Liu, Xinxing
Abstract : DNA and RNA simultaneously extracted from A. f using the optimised method. (a) Total nucleic acid extracted from A. f : lane M1, 1 kb ladder; lane M2, Hind III-cut lambda molecular size marker; lanes 1–4, biological replicates. (b) DNA precipitated by isopropanol. (c) RNA precipitated by LiCl. Abstract : Although many studies have focused on DNA and RNA extraction, only a few have focused on the simultaneous extraction of high quality DNA and RNA from environmental samples, especially for acidic habitat samples. In this study, a widely used DNA extraction method (Zhou, J. Z., M. A. Bruns, and J. M. Tiedje 1996) was optimised for the simultaneous extraction of crude nucleic acid (including DNA and RNA), and a LiCl salt-based step-by-step precipitation method was also optimised for the separation of DNA and RNA. The results showed that nucleic acid extraction buffer (pH 7.0) containing piperazine-1, 4-bis(2-ethanesulfonic acid) (PIPES) salt could effectively extract crude nucleic acid from acidic habitat samples, and the optimised LiCl salt-based step-by-step precipitation method could separate the nucleic acid into high quality DNA and RNA. The results also showed that the obtained DNA and RNA could be used for downstream molecular analysis. This study developed a useful method for the simultaneous extraction and separation of DNA and RNA from acidic habitat samples. This method has a great potential as a standard method to obtain high quality nucleic acid from biohydrometallurgy processes and extreme environmental samples.